2007
DOI: 10.1007/s10157-007-0478-3
|View full text |Cite
|
Sign up to set email alerts
|

Emphysematous cystitis complication in a patient undergoing hemodialysis

Abstract: Emphysematous cystitis is a rare condition characterized by air formation in and around the bladder wall by gas-forming organisms. Although diabetes mellitus and chronic urinary infection, which are frequently encountered in patients with endstage renal disease (ESRD), are predisposing factors for this entity, emphysematous cystitis is actually not common in ESRD patients. Here we provide the first report of a hemodialysis patient who developed typical emphysematous cystitis. Unlike other cases, the emphysemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 9 publications
(4 reference statements)
0
7
0
Order By: Relevance
“…Although pneumaturia appears to be a highly specific symptom, it is a rare patient complaint. Pneumaturia is observed in 70% of patients with bladder catheterization (7,9). Other symptoms of acute cystitis (dysuria, urinary frequency and urinary urgency) occur in approximately 50% of patients.…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…Although pneumaturia appears to be a highly specific symptom, it is a rare patient complaint. Pneumaturia is observed in 70% of patients with bladder catheterization (7,9). Other symptoms of acute cystitis (dysuria, urinary frequency and urinary urgency) occur in approximately 50% of patients.…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…Prevalent symptoms include dysuria, hematuria, increased frequency of urination, fever, suprapubic pain and pneumaturia. Although pneumaturia is a more specific symptom than others, it is quite rare [5]. Thomas et alhave reported that 7% of cases is asymptomatic and incidentally detected by abdominal imaging [2].…”
Section: Discussionmentioning
confidence: 98%
“…A history of pneumaturia is also highly suggestive, but patients rarely report this symptom (14). The diagnosis is provided by radiographic imaging.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that diabetic patients, particularly women presenting with fever of unknown origin, warrant screening for the presence of gas within the bladder. Screening requires not only abdominal CT but also pelvic CT in such patients (14).…”
Section: F I G U R E 2 a C O Mp U T E D T O Mo G R A P H I C S C A mentioning
confidence: 99%
See 1 more Smart Citation